ORNAMEN MELAYU DENGAN MEDIA KACA BIDANG DATAR DITINJAU DARI PRINSIP-PRINSIP SENI RUPA - Edo Wahyu Triawan; Misgiya Misgiya; Nelson Tarigan (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2021)
This study aims to analyze and describe the application of Malay ornaments on flat-plane glass media by class XI SMAS Dharma Karya Beringin students based on the principles of fine arts, especially in the aspects of unity, balance, harmony, center of attention, and rhythm. This study used descriptive qualitative method. The subjects of this research were students of class XI SMAS Dharma Karya Beringin and the object of the research was the Malay ornament work on flat glass media totaling 15 students' works using the Census Sampling technique. The results of this study explain that the mean score of the work as a whole is categorized as good with an average of 84.9 (good). Malay ornament works are assessed based on the aspects of unity, balance, harmony, center of attention, and rhythm. The aspect of assessment with the highest score is the balance with an average score of 85, that is, the similarity of the left and right motives is relatively the same. aspects of harmony with an average value of 85.47, namely the harmony of the motives is well ordered. The aspect of unity with an average score of 85.3, namely the combination of several shapes and motifs that are linked appropriately. The rhythm aspect with an average value of 84.4, namely the order in which the motifs are placed in order and the attention center aspect with an average value of 83.7, namely the shape of the different motifs and placed in the middle. If broken down as a whole based on student achievement, the works with the very good category are 0 ornamental works by 0%. In the good category there are 15 ornament works at 100% and works with enough category are 0 ornament works by 0%.Keywords: overview, ornaments, malay.AbstrakPenelitian ini bertujuan untuk menganalisis dan mendeskripsikan penerapan ornamen Melayu pada media kaca bidang datar karya siswa kelas XI SMAS Dharma Karya Beringin berdasarkan dari prinsip-prinsip seni rupa khususnya dalam aspek kesatuan, keseimbangan, keselarasan, pusat perhatian, dan irama. Penelitian ini menggunakan metode deskriptif kualitatif. Subjek penelitian ini adalah siswa kelas XI SMAS Dharma Karya Beringin dan objek penelitian adalah karya ornamen Melayu pada media kaca bidang datar berjumlah 15 karya siswa dengan menggunakan teknik Total Sampling. Hasil penelitian ini menjelaskan bahwa nilai rata-rata karya secara keseluruhan dikategorikan baik dengan rata-rata 84,9 (baik). Karya Ornamen Melayu dinilai berdasarkan aspek kesatuan, keseimbangan, keselarasan, pusat perhatian, dan irama. Aspek penilaian dengan nilai tertinggi adalah keseimbangan dengan nilai rata-rata 85, yaitu kesamaan motif kiri dan kanan relatif sama. aspek keselarasan dengan nilai rata-rata 85,47, yaitu keserasian motif tertata dengan baik. Aspek kesatuan dengan nilai rata-rata 85,3, yaitu perpaduan beberapa bentuk dan motif tertaut dengan tepat. Aspek irama dengan nilai rata-rata 84,4, yaitu urutan penempatan motifnya sudah tertata dan aspek pusat perhatian dengan nilai rata-rata 83,7, yaitu bentuk motif berbeda dan ditempatkan ditengah. Apabila dirincikan secara keseluruhan berdasarkan capaian siswa maka karya dengan kategori sangat baik berjumlah 0 karya ornamen sebesar 0%. Kategori baik berjumlah 15 karya ornamen sebesar 100% dan karya dengan kategori cukup berjumlah 0 karya ornamen sebesar 0%.Kata Kunci: tinjauan, ornamen, melayu. Authors: Edo Wahyu Triawan : Universitas Nrgeri MedanMisgiya : Universitas Nrgeri MedanNelson Tarigan : Universitas Nrgeri Medan References: Atmojo, W.T. (2013). Penciptaan Batik Melayu Sumatera Utara. Jurnal Seni dan Budaya Panggung, 23(01), 90-97. http://dx.doi.org/10.26742/panggung.v23i1.89.Sukimin, A.W. Sutandur. (2008). Terampil Berkarya Seni Rupa 1. Solo: Tiga Serangkai.Dalijo, D. (1983). Pengenalan Ragam Hias Jawa. Jakarta: Depdikbud.Feldman, E.B. (1967). Art Image and Idea. New Jersey: Prentice Hall Inc.Resita, R.A. Diah, (2010). Ragam Hias Nusantara. Jurnal Humaniora, 1(02), 246-252.Sirait, Baginda. (1980). Pengumpulan dan Dokumentasi Ornamen Tradisional di Sumatera Utara. Medan: IKIP Medan.Sugiyono. (2014). Metode Penelitian Pendidikan. Bandung: Alfabeta.Triawan, E.W. (2020). “Karya Ornamen Melayu Siswa Kelas XI SMAS Dharma Karya di Atas Media Kaca Bidang Datar”. Hasil Dokumentasi Pribadi: 11 November 2020, SMAS Dharma Karya Beringin.Utami, A., Soeprayogi, H., & Azis, A. C. K. (2020).Pembuatan Kerajinan Bunga Berbahan Kulit Jagung Ditinjau dari Prinsip-prinsip Seni Rupa dan Kerajinan. Journal of Education, Humaniora and Social Sciences (JEHSS), 3(1), 260-264. https://doi.org/10.34007/jehss.v3i1.282.